1969
DOI: 10.1007/bf00379826
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chloroplast number per cell during leaf development in spinach

Abstract: The amounts of chlorophyll and nitrogen and the numbers of cells per unit area change as the green leaves of spinach plants grow and increase in size in the light. The changes in the numbers of chloroplasts per cell were measured by a new method. A 5-fold increase in the numbers of chloroplasts per cell took place in both palisade and mesophyll cells over a growing period of 10 days during which time the area of the leaves increased from 1 to 50 cm(2). Proplastids were not present in the young green leaves but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 15 publications
0
33
0
3
Order By: Relevance
“…Plastid numbers per cell were determined by the method of Possingham and Saurer (1969) for leaves which had been fixed in 3% glutaraldehyde for at least 2 h at 4° C. Pieces 2x2 mm were cut from the mid-region of the leaf, avoiding major veins (Bradbeer et aL, 1970), and placed in i N HCl for 10 min at 60° C. The tissue was transferred to 50% glycerol on a slide and teased out with a needle to separate the cells. Excess tissue was removed and the separation of the cells was completed by the application of gentle pressure to the coverslip.…”
Section: Methodsmentioning
confidence: 99%
“…Plastid numbers per cell were determined by the method of Possingham and Saurer (1969) for leaves which had been fixed in 3% glutaraldehyde for at least 2 h at 4° C. Pieces 2x2 mm were cut from the mid-region of the leaf, avoiding major veins (Bradbeer et aL, 1970), and placed in i N HCl for 10 min at 60° C. The tissue was transferred to 50% glycerol on a slide and teased out with a needle to separate the cells. Excess tissue was removed and the separation of the cells was completed by the application of gentle pressure to the coverslip.…”
Section: Methodsmentioning
confidence: 99%
“…However, confirmation that chloroplasts could divide inside developing plant cells was only made in the late 1960s (Possingham and Saurer, 1969). Evidence for chloroplast division arose mainly as a result of improvements in electron microscopy techniques that facilitated the production of images of young chloroplasts with central constrictions (Boasson et al, 1972;Platt-Aloia and Thomson, 1977).…”
Section: Cell Biology Of Plastid Division Cell Biology Of Plastid DIVmentioning
confidence: 99%
“…The population dynamics of chloroplasts have been analyzed in detail in expanding mesophyll cells of young wheat leaves (Boffey et al, 1979;Boffey and Leech, 1982;Dean and Leech, 1982;Ellis et al, 1983;Ellis and Leech, 1985) and spinach leaves (Possingham and Saurer, 1969;Saurer and Possingham, 1970;Cran and Possingham, 1972;Possingham and Smith, 1972;Possingham et al, 1975). These studies showed a correlation between the existence of dumbbell-shaped dividing chloroplasts in cells and a subsequent increase in chloroplast number per cell.…”
Section: Cell Biology Of Plastid Division Cell Biology Of Plastid DIVmentioning
confidence: 99%
“…The overall synthesis of Fraction I protein does appear to be a discrete event in the life-span of a leaf, being limited largely to expanding leaves when the chloroplasts are dividing by fission and increasing in size (Possingham and Saurer, 1969;Honda et al, 1971). The decline of incorporation into Fraction I also appears to coincide with the reduction of incorporation of ^-^P into chloroplastic rRNA and one aspect of the control of Fraction I synthesis in the ageing leaf may be a non-synchronous synthesis of the two sub-units of the protein, the amount of the larger one becoming rate-limiting in the chloroplast as the content of 70S ribosomes decreases.…”
Section: Discussionmentioning
confidence: 99%